2012
DOI: 10.1371/journal.pone.0050683
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin Reductase Deficiency Potentiates Oxidative Stress, Mitochondrial Dysfunction and Cell Death in Dopaminergic Cells

Abstract: Mitochondria are considered major generators of cellular reactive oxygen species (ROS) which are implicated in the pathogenesis of neurodegenerative diseases such as Parkinson’s disease (PD). We have recently shown that isolated mitochondria consume hydrogen peroxide (H2O2) in a substrate- and respiration-dependent manner predominantly via the thioredoxin/peroxiredoxin (Trx/Prx) system. The goal of this study was to determine the role of Trx/Prx system in dopaminergic cell death. We asked if pharmacological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 42 publications
8
63
0
1
Order By: Relevance
“…Cellular resistance to H 2 O 2 in the neuronal phenotype can be explained by the elevated basal antioxidant capacity. Since the RA-induced differentiation decreases levels of TrxR and GSH, this may suggests a role of these antioxidants in 6-OHDA detoxification, as previously described (SotoOtero et al 2000;Lopert et al 2012). Hence, the resistance to 6-OHDA found in undifferentiated cells can be explained, at least in part, by the high GSH levels presented in the tumoral phenotype.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Cellular resistance to H 2 O 2 in the neuronal phenotype can be explained by the elevated basal antioxidant capacity. Since the RA-induced differentiation decreases levels of TrxR and GSH, this may suggests a role of these antioxidants in 6-OHDA detoxification, as previously described (SotoOtero et al 2000;Lopert et al 2012). Hence, the resistance to 6-OHDA found in undifferentiated cells can be explained, at least in part, by the high GSH levels presented in the tumoral phenotype.…”
Section: Discussionsupporting
confidence: 57%
“…The H 2 O 2 detoxification in neuronal cells is catalyzed primarily by thioredoxin and glutathione systems, which are the most important antioxidants in the brain (Lopert et al 2012;Garcia-Garcia et al 2012), hence we found that both models mimic the oxidative neuronal profile.…”
Section: Discussionmentioning
confidence: 59%
“…LDH activity was measured in media and cell lysates collected in a Tris/NaCl lysis buffer containing 0.1% Triton (v/v), as described previously (85). Activity was measured spectrophotometrically at 30°C as the amount of pyruvate consumed, by monitoring the decrease in absorbance because of NADH oxidation at 340 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Yeast cells lacking TrxR have reduced abilities to detoxify oxidants and to repair oxidative damage (Carmel-Harel et al, 2001). Disruption of TrxR elevates oxidative stress, mitochondrial dysfunction, and cell death in dopaminergic cells (Lopert et al, 2012). TrxR inhibitors cause growth inhibition and apoptosis in various cancer cells, indicating a relationship between TrxR inactivation and apoptosis or inhibition of cell growth (Zhao et al, 2005).…”
Section: 미생물학회지 제52권 제1호mentioning
confidence: 99%